A Focus on "Bio" in Bio–Nanoscience: The Impact of Biological Factors on Nanomaterial Interactions. Issue 16 (25th June 2021) - Cortez‐Jugo, Christina; Czuba‐Wojnilowicz, Ewa; Tan, Abigail; Caruso, Frank
Abstract: Bio–nanoscience research encompasses studies on the interactions of nanomaterials with biological structures or what is commonly referred to as the biointerface. Fundamental studies on the influence of nanomaterial properties, including size, shape, composition, and charge, on the interaction with the biointerface have been central in bio–nanoscience to assess nanomaterial efficacy and safety for a range of biomedical applications. However, the state of the cells, tissues, or biological models can also influence the behavior of nanomaterials at the biointerface and their intracellular processing. Focusing on the "bio" in bio–nano, this review discusses the impact of biological properties at the cellular, tissue, and whole organism level that influences nanomaterial behavior, including cell type, cell cycle, tumor physiology, and disease states. Understanding how the biological factors can be addressed or exploited to enhance nanomaterial accumulation and uptake can guide the design of better and suitable models to improve the outcomes of materials in nanomedicine. Abstract : Studies of bio–nano interactions have largely focused on the influence of the physicochemical properties of materials on their interactions with biological systems. This review focuses on the "bio" in bio–nano interactions and highlights the impact of biological factors at the cellular, tissue, and whole organism level on nanomaterial uptake and efficacy.